Autoantibodies from Patients with Scleroderma Renal Crisis Promote PAR-1 Receptor Activation and IL-6 Production in Endothelial Cells - Michèle Simon (MDPI AG, 2021)
Background. Scleroderma renal crisis (SRC) is a life-threatening complication of systemic sclerosis (SSc). Autoantibodies (Abs) against endothelial cell antigens have been implicated in SSc and SRC. However, their detailed roles remain poorly defined. Pro-inflammatory cytokine interleukin-6 (IL-6) has been found to be increased in SSc, but its role in SRC is unclear. Here, we aimed to determine how the autoantibodies from patients with SSc and SRC affect IL-6 secretion by micro-vascular endothelial cells (HMECs). Methods. Serum IgG fractions were isolated from either SSc patients with SRC (n = 4) or healthy individuals (n = 4) and then each experiment with HMECs was performed with SSc-IgG from a separate patient or separate healthy control. IL-6 expression and release by HMECs was assessed by quantitative reverse transcription and quantitative PCR (RT-qPCR) and immunoassays, respectively. The mechanisms underlying the production of IL-6 were analyzed by transient HMEC transfections with IL-6 promoter constructs, electrophoretic mobility shift assays, Western blots and flow cytometry. Results. Exposure of HMECs to IgG from SSc patients, but not from healthy controls, resulted in a time- and dose-dependent increase in IL-6 secretion, which was associated with increased AKT, p70S6K, and ERK1/2 signalling, as well as increased c-FOS/AP-1 transcriptional activity. All these effects could be reduced by the blockade of the endothelial PAR-1 receptor and/or c-FOS/AP-1silencing. Conclusions. Autoantibodies against PAR-1 found in patients with SSc and SRC induce IL-6 production by endothelial cells through signalling pathways controlled by the AP-1 transcription factor. These observations offer a greater understanding of adverse endothelial cell responses to autoantibodies present in patients with SRC.